Measles in HIV-infected children in southern Africa - A.M. Sheikh; P. Patel; L. Scherzer; C.P. Neumann; G. Anabwani; M.A. Tolle (South African Family Practice)
In recent years, southern Africa has experienced a widespread measles outbreak. Given the high human immunodeficiency virus (HIV) prevalence in the region, the particular features of measles in HIV-infected individuals are of interest to clinicians, especially as regards children, as are measles immunisation strategies for this population. This review discusses a case of severe measles in an HIV-infected child in Botswana, focusing on its implications for clinical case management in Botswana and similar settings and for policies on measles immunisation.